Skin disease profile of Syrian refugees in Jordan: a field‐mission assessment. (17th October 2019) - Saikal, S.L.; Ge, L.; Mir, A.; Pace, J.; Abdulla, H.; Leong, K.F.; Benelkahla, M.; Olabi, B.; Medialdea‐Carrera, R.; Padovese, V.
Abstract: Background: Since the beginning of the Syrian war in 2011, the world has faced the most severe refugee crisis in history and 5.6 million Syrians have sought asylum in neighbouring countries or in Europe. According to recent estimates, more than 650 000 Syrian refugees are displaced in Jordan. Objectives: This article aims to assess the demographic characteristics and skin disease profile of Syrian displaced people residing in Al Za'atari camp and in communities in Jordan. Furthermore, the authors discuss the barriers to healthcare provision experienced during field missions. Methods: This is a retrospective analysis of medical records collected during three medical missions in Jordan by an international dermatological team. Data on patient age, gender, country of origin and skin disease diagnoses were recorded both in Al Za'atari camp and Jordanian towns near the Syrian border. Results: A total of 1197 patients were assessed during the field missions, with 67.7% female and 37.1% under the age of 14 years. Dermatitis was the leading dermatological condition in both refugee camp and community healthcare clinics. Infectious diseases were the second most common; however, fungal presentations were more common in the community as opposed to viral in Al Za'atari. Conclusions: High dermatitis presentations were likely secondary to the environment, living conditions and lack of access to emollients. Infectious diseases were postulated secondary to poor hygiene and sharing of overcrowded spaces. Barriers to health care included limited pharmacological formulary, difficulty in continuity of care and case referrals due to lack of specialized services. Better access to health care, improvement of living conditions and hygiene, and increased availability of medications including emollients and sunscreens are all interventions that should be carried out to reduce skin disease burden. Our findings should further urge the international community to uphold their commitments and uptake engagement in improving health care for Syrian displaced people.